Assessment of University Campus Cafe Service: The Students Perceptions - Shanka, Tekle; Taylor, Ruth (Routledge, 2005)
This paper presents the results of a study conducted to examine the important attributes in food service provision on a large Australian university campus. Ten café outlets (A to J to maintain anonymity of the café outlets) positioned across a large university campus located in an urban residential area were surveyed. A total of 410 students participated in the survey. Based on the frequency of patronage to the cafés results showed that five of the ten café outlets were more frequently visited in a given week. These were Café A, Café B, Café H, Café F, and Café I; however, the focus of this paper would be on Café A, which was just recently opened for business. Results indicated that students considered quality, price and service as the most important attributes in patronizing a particular café on campus. Results also indicated that students were most satisfied with important attributes such as convenience, ambience and quality during their visit to the café. Paired samples' t-test results showed statistically significant differences between the perceived importance and level of satisfaction with all attributes except the opening hours attribute. Results are discussed with possible implications and suggestions for further research.